Multiresistant Citrobacter freundii as an etiological agent of urinary tract infection - Carmen Ullauri-González; Sandra Freire-Cuesta (Kasmera, 2019)
Citrobacter freundii, sometimes it can act as opportunistic pathogen, a case of this isolated microorganism is presented as an etiological agent of urinary tract infection, in a patient with chronic obstructive pulmonary disease. The isolate was multiresistant to gentamicin, amikacin, trimetoprim sulfamethoxazole, ciprofloxacin, ceftriaxone, ceftazidime, cefepime, imipenem, meropenem and doripenem and it was susceptible to tigecycline and colistin, the molecular analysis showed the presence of the blaKPC gene.